Chaos and confusion with confidence: Managing fear of Re-Injury after anterior cruciate ligament reconstruction. (September 2020) - Mahood, Ciaran; Perry, Meredith; Gallagher, Peter; Sole, Gisela
Abstract: Objectives: To explore strategies enabling competitive athletes to manage re-injury fears or anxieties, facilitating return to competitive sport following anterior cruciate ligament reconstruction (ACLR). Design: Qualitative study. Setting: University. Participants: Ten athletes with ACLR within the last 5 years who had returned to competitive sport with a minimum 7/10 Tegner Activity score. Methods: Semi-structured interviews, recorded, transcribed and analysed using interpretive description. Results: Three main themes. "Driving reasons to return to sport" included the athletic identity, the competitive team spirit and commitment; "Preparation of body and mind" encompassed connectedness with health professionals, coaches, the sports team and family, graded exposure and progression of physical tasks, and psychological or cognitive skills to improve mental toughness; "Risk Acceptance" entailed situational risk analysis, problem solving, and avoidance of unacceptable risk and acceptance of risk and responsibility. Conclusion: Participants described intrinsic and extrinsic motivators as drivers for rehabilitation. Interactions with therapists, coaches and team members enhanced confidence, supported by both physical rehabilitation and psychological influences. Psychological strategies were essential for several participants to return to sport. Graded sports exposure, leading towards total immersion in training and competition, appears important to manage re-injury fear following ACLR. Highlights: We explored athletes' strategies to return to competitive sports following ACLR. Participants described strong athletic identities and commitment to the team. Social and professional connections with others facilitated return to sports. They used instantaneous situational risk assessments while playing and competing. They needed to be prepared for 'chaos and confusion' to focus the game.